Visual Inspection as a Screening Method in Assembly Process for Quality Improvement - Soufhwee, A.R.; Mahmood, W. H. W.; Abdullah, M.I.H.C. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Kaizen is one of the famous approach in the Japanese manufacturing industries to increase the productivity. There are many techniques applied in Kaizen, but surprisingly the visual inspection ‘point to point checking jig’ is a potential technique to respond customer needs in term of quality issue. This study is performed to detect missing rivet pin during riveting process manually done by operators. The root cause of this the quality issue is due to lack of awareness among the operators. ‘Point to point checking jig’ is apply in order to eliminate waste at production line related to the manually process by operators. Plan, Do, Check and Action or known as PDCA is a method that has been applied in this study. The point to point jig was designed and fabricate with characteristics of mistake proofing. 50 samples were prepared as a pilot run to monitor and validate the progress action. This procedure is to ensure zero percentage (0 %) defect target was achieved in the following months after correction action had been taken. This paper shows the successful of ‘point to point checking jig’ in Kaizen, which gives impact to product quality performance.